Enhancing routine HIV and STI testing among young men who have sex with men: primary outcomes of the get connected clinical randomized trial (ATN 139) - J.A. Bauermeister; K.J. Horvath; W.Y. Lin; J.M. Golinkoff; K.F. Claude; N. Dowshen; M. Castillo; P.S. Sullivan; M. Paul; L. Hightow-Weidman; R. Stephenson (BMC, 2024)
Abstract Background Regular HIV and STI testing remain a cornerstone of comprehensive sexual health care. In this study, we examine the efficacy of Get Connected, a WebApp that combines test locators with personalized educational resources, in motivating young men who have sex with men (YMSM) to undergo regular HIV and STI testing. Methods Participants were randomly placed in one of two conditions. The first condition included the full version of GC (GC-PLUS), which included content tailored to users' psychosocial characteristics (e.g., age, race/ethnicity, relationship status, HIV/STI testing history). The second condition served as our attention-control and only included the testing locator (GC-TLO) for HIV/STI testing services. Participants were recruited from three cities (Houston, Philadelphia, and Atlanta) characterized by high HIV incidence. Assessments were collected at 1, 3-, 6-, 9- and 12-month follow-ups. Results Both versions of GC were acceptable and efficacious in increasing routine HIV and STI testing over a 12-month period. 40% of the sample reported testing at least twice, with no main effects observed across the two intervention arms (OR = 1.11; 95% CI: 0.69, 1.80), p =.66). Greater intervention effects were observed among YMSM who engaged more frequently with the intervention, with regional differences observed. Conclusions Our findings underscore the need to cater to the diverse needs of YMSM through multilevel approaches. Broadly, mHealth HIV/STI testing interventions, such as Get Connected, would benefit from matching technologies to the local context to have the greatest impact. Trial Registration This study is registered on ClinicalTrials.gov (NCT03132415).